Statistics and machine learning methods for EHR data : from data extraction to data analytics - Wu, Hulin; Yamal, Jose-Miguel; Yaseen, Ashraf; Maroufy, Vahed (Boca Raton : CRC Press, 2020)
"The book carefully evaluates and compares the standard statistical models and approaches with those of machine learning and deep learning methods and reports the unbiased comparison results for these methods in predicting clinical outcomes based on the EHR data"--
Introduction: Use of EHR data for scientific discoveries-challenges and opportunities / Hulin Wu -- EHR project management / Yashar Talebi and Ashraf Yaseen -- EHR databases and data management : data query and extraction / Gen Zhu, Vi K. Ly, Michael Gonzalez, Leqing Wu, Hulin Wu, and Ashraf Yaseen -- EHR data cleaning / Yashar Talebi, Han Feng, Yuefan Huang, and Vahed Maroufy -- EHR data pre-processing and preparation / Duo Yu, Xueying Wang, and Hulin Wu -- EHR missing data issues / Chenguang Zhang, Vahed Maroufy, Baojiang Chen, and Hulin Wu -- Causal inference and analysis for EHR data / Stacia DeSantis, Momiao Xiong, Jose-Miguel Yamal, Gen Zhu, Duo Yu, Xueying Wang, Chenguang Zhang, and Vi K. Ly -- EHR data exploration, analysis and predictions : statistical models and methods / Gen Zhu, Frances Brito, Stacia M DeSantis, and Vahed Maroufy -- Neural network and deep learning methods for EHR data / Duo Yu, Ashraf Yaseen, and Xi Luo -- EHR data analytics and predictions : machine learning methods / Yuxuan Gu, Yuefan Huang, Vi Ly, Ashraf Yaseen, and Hongyu Miao -- Use of EHR data for research : future / Hulin Wu.
OCLC-licensed vendor bibliographic record.
Keywords: Medical records -- Data processing; Machine learning; BUSINESS & ECONOMICS / Industries / Service Industries; COMPUTERS / Database Management / Data Mining; MATHEMATICS / Probability & Statistics / General